Predicting food waste in households with children: socio-economic and food-related behavior factors - Tonini, Pietro; Odina, Pere Muñoz; Durany, Xavier Gabarrell (Frontiers in Nutrition, 2023)
The consumption phase accounts for approximately half of the food waste generated within the food system. Numerous studies have identified families with children as the primary contributors to food waste. The aims of this paper is to enhance the comprehension of food waste behaviors in households with children by characterizing it and studying how socioeconomic characteristics and food-related behaviors can predict it.Methods: A survey was conducted among 806 families with children, categorized by the child's age and family structure. The study utilized descriptive statistics to summarize the food waste behaviors and binary regression to evaluate the predictive abilities of 12 variable related to the socio-economic characteristic, purchase, and preparation behaviors and diet quality factors.Results: Perishable food items, such as fruits, vegetables, cereal-based product, and dairy products, were the primary items wasted in households with children. Two patterns of food waste were identified: inadequate food management leading to small amounts of waste in families with young and middle-aged children, and over-purchasing perishable items leading to waste in other households with children. Household type and purchasing habits were significant predictors, while the purchaser's age and buying channel showed lower predictive capacity.Discussion: Policies to reduce food waste should prioritize raising awareness among children, promoting good practices at the household level, and creating favourable conditions during purchases. Strategies include enlisting children's participation in meal planning and